Penerimaan Diri Pada Remaja Dengan Orang Tua Poligami - Rahmawati, Fikrotul Ulya, Dr. Wiwien Dinar P, M.Si, Psi (2017)
The aim of this study are to determine and describe about the self-acceptance in adolescents parents did polygamy. This study used qualitative approach, the data were collected by interview. The informant in this study are five adolescents aged 13-21 years old, informant criteria in this study is adolescents whose father did polygamy. This research result indicates that teenager was an informant in this research have not received the state of himself . It indicated by a feeling of shame ,sad,disappointed and deplored the decision taken by his father. In addition, informants felt dissatisfied with his life by lack of responsibility father to family, the frequent meetings with the father reduced, mercy family reduced, and the economy family being unbalanced. Factor that influences self acceptance in adolescents whose father polygamy of them the response negative of the neighborhood after the father informants did polygamy , the pressures of friends informants who makes social interaction informants slightly disturbed. The impact of polygamy of them are the decrease confidence in informants to interact with their surroundings, the decrease concentrate on informants in seek the education. Nevertheless there are individual able to accept the condition shown by its ability to stay in failure or pain and can cope with the circumstances of emotional condition as depression, angry, and guilt. One individual who could receive a response his father did polygamy because any theories parents with a base religion